International Advanced Technology Congress, Dec 6-8 2005, Putrajaya, Malaysia : meeting challenges in globalization through advanced technology.
Includes paperwork from CAM 2005, iCISAR 2005, CoBE 2005, SPACE 2005, CATS 2005, ConCIS 2005 AND CoAT 2005.